PWE-426 Hepatology training in the uk – results from the bsg training survey 2014. (22nd June 2015) - Corrigan, M; Alzoubaidi, D
Abstract : Introduction: Issues around hepatology service delivery and training in the UK have been highlighted by the recent Lancet Commission. 1 Currently, the majority of liver services are delivered by gastroenterologists with <6 months of hepatology. Increased numbers of specialists with advanced training are required to tackle the increasing burden of liver disease. Whilst guidelines exist to define minimum training requirements and competencies for all trainees, 2 training opportunities are variable. Method: The 2014 trainee survey was sent to all UK trainees. 263/806 (32.6%) responded. Within the hepatology section of the survey, respondents were asked about future career plans, satisfaction with training, training opportunities and self assessed competence. Results: Subspecialism: 8% of trainees plan to be a subspecialist hepatologist and 6% an academic hepatologist which is lower than those planning a career in general gastroenterology (16%), advanced endoscopy (12%) and IBD (10%). Overall experience: 68% of respondents rated themselves as either satisfied/very satisfied with their hepatology training. This is lower (p < 0.01) than overall gastroenterology training (82.9%), basic endoscopy (79.9%) and IBD (79.2%). Barriers to training: 25.3% of trainees who wished to undertake formal hepatology training identified a barrier to accessing this. The main barriers were lack of local training opportunities and not wishing to move region to access hepatology training. Opportunities: All trainees should have at least 12 months in a level 2 or 3 centre. 2 However of current senior trainees (ST6+) less than 70% reported spending 6 months or more in at least one of these centres. Self reported competence of senior trainees to act as a consultant in a district general hospital found that 50% felt they were not competent in post transplant, viral and autoimmune liver disease and 30% felt they were not competent managing complications of portal hypertension including variceal bleeding. Conclusion: The results confirm variability in hepatology training. This exists not only in access to advanced training but also core training competencies. All deaneries should aim to organise training rotations to maximise the opportunities especially in the deaneries which do not contain a level 3 centre. Early exposure of all trainees to hepatology units and clinics may allow better understanding of training pathways and early career planning. Disclosure of interest: None Declared. References: Williams R, Aspinall R, Bellis M, Camps-Walsh G, Cramp M, Dhawan A, et al . Addressing liver disease in the UK: a blueprint for attaining excellence in healthcare and reducing premature mortality from lifestyle issues of excess consumption of alcohol, obesity and viral hepatitis. Lancet 2014;384(9958):1953–1997 BSG Liver Section Training information 2014. http://www.bsg.org.uk/sections/liver-training/index.html